2010
DOI: 10.1677/erc-10-0007
|View full text |Cite
|
Sign up to set email alerts
|

SOCS-3 antagonises the proliferative and migratory effects of fibroblast growth factor-2 in prostate cancer by inhibition of p44/p42 MAPK signalling

Abstract: Fibroblast growth factor-2 (FGF-2) is highly expressed in prostate cancer. It promotes tumour progression through multiple pathways including those of signal transducers and activators of transcription factor 3 (STAT3), mitogen-activated protein kinases (MAPKs) and Akt. In previous studies, we have reported that STAT3 phosphorylation inversely correlates with suppressor of cytokine signalling-3 (SOCS-3) expression in prostate cancer cells. Recently, it has become evident that SOCS-3-negative regulation is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 51 publications
(65 reference statements)
1
29
0
Order By: Relevance
“…In addition, the inhibition of MEK1/2 by U0126 suppressed the migration of cholangiocarcinoma cells treated with bFGF. These results are consistent with a recent study that demonstrated the activation of the p44/p42 MAPK pathway, but not the Akt or STAT pathways, following bFGF stimulation (19). To the best of our knowledge, this is the first study to demonstrate the signal transduction pathways of bFGF/FGFR in cholangiocarcinoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the inhibition of MEK1/2 by U0126 suppressed the migration of cholangiocarcinoma cells treated with bFGF. These results are consistent with a recent study that demonstrated the activation of the p44/p42 MAPK pathway, but not the Akt or STAT pathways, following bFGF stimulation (19). To the best of our knowledge, this is the first study to demonstrate the signal transduction pathways of bFGF/FGFR in cholangiocarcinoma cells.…”
Section: Discussionsupporting
confidence: 93%
“…The FGF family consists of 23 members (FGF-1-23); FGF-23 was originally identified as a novel member of this FGF family (Puhr et al, 2010) and is generally recognized as a bone-derived protein that is mainly secreted by osteoblasts and osteocytes in adults (Oikonomou et al, 2013). 4015.3 ± 3055.6 3021.0 ± 2388.7* cTnI (ng/mL) 0.3 ± 0.1 0.1 ± 0.1* P 3+ (mM) 2.5 ± 0.8 1.7 ± 0.6* *P < 0.05, compared with PD patients without LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of SOCS3 causes cell death of prostate cancer through activation of the extrinsic and intrinsic apoptosis pathways [11]. The underlying mechanism is that SOCS3 antagonizes the proliferative and migratory ability in prostate cancer by inhibition of p44/p42 MAPK signaling [12]. In addition, SOCS3 inhibit the signal transducer and activator closely related to Pca cell proliferation and invasiveness, such as transcription 3 (STAT3) [13,14,15], nuclear factor kappa B (NF-κB) [16] and activation protein 1(AP1) [17].…”
Section: Introductionmentioning
confidence: 99%